PENGARUH KEGIATAN MELUKIS DENGAN BARANG BEKAS TERHADAP PERKEMBANGAN KREATIVITAS ANAK 5-6 DI TK KASIH BAPA PERCUT SEI TUAN: Penelitian Kuantitatif - Sondang Kiki Febrianti Pane; Elya Siska Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The aim of this study was to investigate the effects of painting using used objects. The kind of quantitative research with an experimental approach. This study uses a pre-experimental design called the One Group pretest-postest. The population in this study was all children of group B. where students were 8 males and 12 females. Research variables are painting activities using free objects (free variables) and children's creativity (bound variables). This research is based at Father Percut Sei's School. The techniques of collection, observation and documentation, From the final test results that have been performed, are derived an average score of pretest result 34, whereas a posttest average is 44. So the conclusion of this study is that there was an influence of painting activities with used items on creativity development in 5-6 year old children at Tk Kasih Bapa Percut sei Tuan.